Key technology and application of intelligent connected patrol vehicles for security scenario - Yuchao LIU; Ziyue LI (Dianxin kexue)
Practical applications combined with industry scene is a common problem in the present artificial intelligence technology.Facing the security application scenario,the practice landing of unmanned technology -- intelligent connected patrol vehicle was studied.Integrating different sensors such as camera,LiDAR,inertial navigation system (INS),etc,the awareness system can accurately identify the platform itself,road conditions and target behavior using key technology such as artificial intelligence (AI),data fusion.Combining human intelligence (HI) in scene cognition of human experience and artificial intelligence (AI) in cognition of computing,a hybrid intelligent cognitive system using to security scene was built.Based on human in the loop system architecture and technology such as 5G ,vehicle to everything (V2X),edge computing,etc,different interactions between human ,machine and environment were designed,which ensured the safe and reliable operation of the system and increased the work efficiency by a wide margin.